1998
DOI: 10.1046/j.1460-9568.1998.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of a human auditory cortex area involved in foreground–background decomposition

Abstract: Auditory foreground-background decomposition is a pattern recognition process which combines simultaneous and sequential grouping in complex sound sequences. Using functional magnetic resonance imaging with reduced scanner noise and stimulation through a new type of earphones, we investigated the possibility that this process activates topographically distinct areas of human auditory cortex. A basic matching-to-sample task with variable tones (sequential grouping) caused significant activity in three separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 33 publications
9
44
0
1
Order By: Relevance
“…The DIC selective response was observed in the medial portion of A2 (A2m) as well as in restricted regions of PT and ST (PT␤ and ST␤, respectively), whereas the lateral portion of A2 (A2l) and other regions in PT and ST (PT␣, ST␣, and STa) did not show such selectivity. A recent fMRI study has identified areas of T1b, T2, and T3 in the supratemporal plane (Scheich et al, 1998), which may correspond to A1, A2, and PT in our study, respectively. The present study further revealed functional parcellation within A2, PT, and ST.…”
Section: Functional Differentiation In Multiple Auditory Areasmentioning
confidence: 76%
“…The DIC selective response was observed in the medial portion of A2 (A2m) as well as in restricted regions of PT and ST (PT␤ and ST␤, respectively), whereas the lateral portion of A2 (A2l) and other regions in PT and ST (PT␣, ST␣, and STa) did not show such selectivity. A recent fMRI study has identified areas of T1b, T2, and T3 in the supratemporal plane (Scheich et al, 1998), which may correspond to A1, A2, and PT in our study, respectively. The present study further revealed functional parcellation within A2, PT, and ST.…”
Section: Functional Differentiation In Multiple Auditory Areasmentioning
confidence: 76%
“…FM sweeps are relatively powerful stimuli eliciting strong blood oxygenation level dependent (BOLD) responses in the primary and secondary auditory cortical areas that have been previously distinguished on the dorsal surface and lateral aspect of the superior temporal gyrus Scheich et al, 1998;Baumgart et al, 1999;Brechmann et al, 2002;Deike et al, 2004). Using a low-noise fMRI scanning procedure, the comparison of exposure-related activation with silent intervals between stimulus blocks showed across subjects either an even distribution of activity between the two hemispheres or a more left-lateralized AC activation (Fig.…”
Section: Directional Categorization Of Fm In Human Acmentioning
confidence: 97%
“…Voxels were attributed as activated if the significance level was below 0.05 and if they belonged to a cluster of at least eight contiguous voxels. These clusters in each slice were attributed to one of four territories TA, T1, T2, and T3 defined as previously described (Brechmann et al, 2002;Scheich et al, 1998). For each territory in each subject and each condition, the total number of activated voxels was multiplied by their average relative BOLD signal intensity, resulting in intensity weighted volumes (IWV).…”
Section: Individual Regions Of Interest [Roi] Analysismentioning
confidence: 99%